2014
DOI: 10.2147/tcrm.s62574
|View full text |Cite
|
Sign up to set email alerts
|

Double-balloon tamponade in the management of postpartum hemorrhage: a case series

Abstract: To show the efficacy of double-balloon cervical ripening catheter in the management of postpartum hemorrhage originating from the lower segment of the uterus or the upper parts of the vagina.MethodsPatients with intractable bleeding from the lower segment of the uterus and the upper parts of the vagina after Cesarean or vaginal deliveries were treated by double-balloon cervical ripening catheter.ResultsDouble-balloon catheter was used in seven patients, and it was properly placed in all of them. No other inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…In recent papers, surgical treatment of LUSA was described by means of different methods like: curettage, embolisation, vaginal packing, bilateral cervix apex clamping, transvaginal cervicouterine artery ligation, double balloon tamponade, obstruction of vascularisation by means of uterine traction towards vagina, "holding the cervix" technique, " shing for the balloon shaft" and perpendicular compressive cervical stitches and nally hysterectomy [6,9,[10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Panda et al [6] in 2009. published very appreciable paper about clinical entity known as primary LUSA that should be clearly distinguished from corporeal uterine atony.…”
Section: Discussionmentioning
confidence: 99%
“…In recent papers, surgical treatment of LUSA was described by means of different methods like: curettage, embolisation, vaginal packing, bilateral cervix apex clamping, transvaginal cervicouterine artery ligation, double balloon tamponade, obstruction of vascularisation by means of uterine traction towards vagina, "holding the cervix" technique, " shing for the balloon shaft" and perpendicular compressive cervical stitches and nally hysterectomy [6,9,[10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Panda et al [6] in 2009. published very appreciable paper about clinical entity known as primary LUSA that should be clearly distinguished from corporeal uterine atony.…”
Section: Discussionmentioning
confidence: 99%
“…The success rates were not significantly different when these therapies were used after the failure of UTB. The study shows that even after these interventions, nearly one fourth of the women that had a hysterectomy for final control of the hemorrhage [15].…”
Section: Introductionmentioning
confidence: 92%
“…The success rates were not significantly different when these therapies were used after the failure of UTB. The study shows that even after these interventions, nearly one fourth of the women that had a hysterectomy for final control of the hemorrhage [15].Internal Iliac Artery Ligation has been defined as an efficient method to control untreatable PPH and prevention of maternal death. The justification for these stands on the Burchel hemodynamic studies that showed a 45% reduction on the pelvic blood flow and the pulse pressure on an 85%, which results in increase on the blood venous pressure in the arterial circuit promoting hemostasis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It refers to a condition where the volume of hemorrhage of puerpera exceeds 500 mL within 24 h after delivery of the fetus. Sometimes, the amount of hemorrhage of puerpera after cesarean delivery may be more than 1000 mL within 24 h, and the increased amount of hemorrhage may be accompanied by hypovolemia [3,4]. In addition, postpartum erythrocyte loss of up to, or more than 10 % is considered as postpartum hemorrhage.…”
Section: Introductionmentioning
confidence: 99%